THE ROLE OF ATTACHMENT PARENTING, EDUCATIONAL PROGRAMS, AND PATERNAL EXEMPLARITY IN SHAPING THE CHARACTER OF COMMUNITY LEADERS IN RIAU PROVINCE - Azhar, Edi; Husti, Ilyas; Anwar, Khairil (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: This study explores the role of attachment parenting, educational programs, and paternal exemplarity in shaping the character of community leaders in Riau Province. The research is grounded in the understanding that fathers hold a central role in moral and religious education, serving not only as family heads but also as primary educators who model Islamic values through daily behavior. Purpose: The study aims to examine how emotional attachment, consistent religious guidance, and exemplary conduct contribute to the formation of virtuous character among children who later become influential figures in their communities. Method: Using a qualitative descriptive approach, data were collected through in-depth interviews with five community leaders representing diverse backgrounds. The analysis employed an interpretative framework of Islamic parenting and character education theory. Result: The findings reveal that attachment parenting, when aligned with Islamic principles of affection, discipline, and consistency, fosters emotional security and moral resilience in children. Moreover, fathers who serve as moral exemplars strengthen their children’s sense of responsibility, integrity, and faith-based leadership. Educational programs emphasizing religious values further reinforce these formative experiences. In conclusion, the study highlights that the harmonious integration of emotional closeness, spiritual education, and role modeling plays a crucial role in cultivating individuals with strong faith, noble character, and social responsibility traits essential for community leadership in the contemporary era.